Reengineering Green Education in the Context of Sustainable Development: A Conceptual Framework and Strategic Analysis of Educational Policies and Programs (Al-Farooq Journal of Sciences, 2026)
Amid accelerating global environmental challenges and the growing urgency of achieving the Sustainable Development Goals (SDGs), green education has emerged as a strategic approach for transforming educational systems and promoting sustainable societal development. This study aims to develop an integrated conceptual and strategic framework for reengineering green education through a comprehensive analysis of existing educational policies and programs and by identifying the structural gaps that hinder educational institutions from effectively responding to contemporary environmental, technological, and developmental challenges.The study adopts an integrated descriptive-analytical approach supported by educational policy analysis. It draws upon peer-reviewed academic literature, specialized references, and international reports issued by UNESCO, the United Nations, UNDP, the World Bank, and other relevant organizations. In addition, comparative analysis was employed to examine emerging global practices in green education, environmental governance, digital transformation, and green skills development.The findings reveal a strong interdependent relationship between educational process reengineering and the achievement of sustainable development objectives. The study identifies significant legislative, organizational, technological, knowledge-based, and financial gaps that continue to constrain the transition toward green educational systems. Furthermore, the results highlight that digital transformation, environmental governance, institutional innovation, and sustainable quality assurance constitute essential pillars for successful educational transformation.Based on these findings, the study proposes a strategic model and an implementation-oriented policy matrix for reengineering green education. The proposed framework encompasses regulatory reform, curriculum redesign, smart low-carbon educational environments, green research and innovation support, and multi-stakeholder partnerships. The study concludes that sustainable educational transformation requires a holistic institutional approach capable of developing human capital equipped with green competencies and leadership skills necessary to address future environmental, economic, and social challenges.
Keywords: Green Education; Sustainable Development; Educational Reengineering; Educational Policy; Digital Transformation; Environmental Governance; Green Innovation; Institutional Sustainability